Sufism and deconstruction : a comparative study of Derrida and Ibn ʻArabi - Almond, Ian, 1969- (Routledge studies in religion., 2004)
This book examines a series of common featuress in the works of Derrida and the Sufism of Ibn 'Arabi, considered to be one of the most influential figures in Islamic thought.